1979
DOI: 10.1073/pnas.76.4.1833
|View full text |Cite
|
Sign up to set email alerts
|

Superinduction of alpha 2u globulin by actinomycin D: evidence for drug-mediated increase in alpha 2u mRNA.

Abstract: Actinomycin D, an inhibitor of DNA-dependent RNA synthesis, increased the hepatic concentration of a2u globulin, an androgen-inducible protein in the rat. Spayed female rats with a marginally induced state of a2u synthesis showed an approximately 5-fold increase in hepatic a2u globulin within 3-6 hr after treatment with actinomycin D. Initial treatment of these animals with 5a-dihydrotestosterone, followed by actinomycin D, resulted within 2-3 hr in a more than 2-fold increase in hepatic a2u globulin compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Additional experiments with AM provided evidence for AM-mediated superinduction of metal-induced MT synthesis analogous to effects of AM reported in other inducible systems (Tomkins et al, 1969(Tomkins et al, , 1972Steinberg et al, 1975a;Chatterjee et al, 1979). When 2 µg/mL AM is added to maximally induced Cdr cells (2µ Cd2+ for 8 h; Figure 5A), the MT synthesis rate is increased significantly relative to that in the AM-free control cells.…”
Section: Quantitation Of Metallothioneinsupporting
confidence: 76%
See 1 more Smart Citation
“…Additional experiments with AM provided evidence for AM-mediated superinduction of metal-induced MT synthesis analogous to effects of AM reported in other inducible systems (Tomkins et al, 1969(Tomkins et al, , 1972Steinberg et al, 1975a;Chatterjee et al, 1979). When 2 µg/mL AM is added to maximally induced Cdr cells (2µ Cd2+ for 8 h; Figure 5A), the MT synthesis rate is increased significantly relative to that in the AM-free control cells.…”
Section: Quantitation Of Metallothioneinsupporting
confidence: 76%
“…Although a considerable controversy has surrounded quantitative interpretation of the results of some applications of this inhibitor (cf. Chatterjee et al, 1979), the use of AM to inhibit general RNA synthesis or nucleolar RNA synthesis, specifically, has proven fruitful in numerous studies and has been applied extensively in the investigation of inducible systems (Tomkins et al, 1972;Killewich et al, 1975;Steinberg et al, 1975a;Chatterjee et al, 1979). In the present study, it was found (Table I) that induction of MT synthesis is inhibited not only by a high level of AM (2.0-5.0 µg/mL), which blocks all RNA synthesis, but also by a low level of AM (0.05 gg/mL), which preferentially inhibits nucleolar RNA synthesis (Perry & Kelly, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Neither ca2u-g nor its corresponding mRNA is detectable in the livers ofsexually intact female rats (69,74,75). However, a very low background level ofthe mRNA has been indicated in the ovariectomized female rat (76), and ovariectomy in concert with androgen treatment induces a parallel increase in a2u-g and its mRNA in female rat liver (67,74).…”
Section: The A-globulin Superfamily Of Proteinsmentioning
confidence: 99%
“…As indicated earlier, extensive research on the DNA-specific intercalator actinomycin D indicates the diversity of action in vivo . Actinomycin D was found to be a super inducer of the synthesis of some animal genes ( Chatterjee et al, 1979 ). In an early screening of intercalators, we found actinomycin D and other intercalators to be strong activators of plant defense responses ( Schwochau and Hadwiger, 1968 ).…”
Section: Variation In Dna-specific Agents Actionmentioning
confidence: 99%